Effect of Tannin-Rich Extract of Chasmanthera dependens on Piroxicam-induced Liver Damage in Male Wistar Rats - Tijani Stephanie Abiola; Olori Ogaraya David; Farombi Ebenezer Olatunde (Molecular and Cellular Biomedical Sciences, 2021)
Background: Piroxicam is one of the nonsteroidal anti-inflammatory drugs used as antipyretic, analgesic and anti-inflammatory drug often used for the relief of nonspecific fever condition and in arthritis. This study investigated the protective potential of tannin-rich extract of Chasmanthera dependens (TRECDS) against piroxicam-induced hepatotoxicity in male Wistar rats.Materials and Methods: Thirty two rats were divided into four groups. Group 1 received normal saline and served as the control group, group 2 were given 20 mg/kg piroxicam only, while groups 3 and 4 were given 20 mg/kg piroxicam with the addition of 200 and 400 mg/kg of tannin-rich extract of Chasmanthera dependens, respectively. All rats were treated orally once daily for ten days.Results: Administration of piroxicam caused liver atrophy demonstrated by significant rise in serum alanine aminotransferase (ALT), alkaline phosphatase (ALP), aspartate aminotransferase (AST), gamma-glutamyl transferase (GGT), glucose-6-phosphate dehydrogenase (G6PDH) levels of albumin (ALB), bilirubin (BIL), total cholesterol (TCHOL), triglyceride (TRIGS) and low-density lipoprotein (LDL). Piroxicam also decreased high-density lipoprotein (HDL) level, enzymatic and nonenzymatic antioxidant levels significantly (p>0.05) with attendant increase in oxidative stress indices in the liver of rats compared with control group. Histological assessment reveled severe damaged to the liver of rats. However, co-administration with TRECDS reversed these observations as evidenced in the histological results.Conclusion: The findings of this study showed that exposure of rats to piroxicam provoked damage to the liver via oxidative damage and TRECDS has the potential of ameliorating the damage.Keywords: hepatotoxicity, piroxicam, Chasmanthera dependens, oxidative stress